2021
DOI: 10.1101/2021.04.30.21256119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between oral anticoagulants and COVID-19 related outcomes: two cohort studies

Abstract: ObjectivesWe investigated the role of routinely prescribed oral anticoagulants (OACs) in COVID-19 outcomes, comparing current OAC use versus non-use in Study 1; and warfarin versus direct oral anticoagulants (DOACs) in Study 2.DesignTwo cohort studies, on behalf of NHS England.SettingPrimary care data and pseudonymously-linked SARS-CoV-2 antigen testing data, hospital admissions, and death records from England.ParticipantsStudy 1: 70,464 people with atrial fibrillation (AF) and CHA□DS□-VASc score of 2. Study 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Of the AF cohort analysed, 8% (n=77,364) had a recorded COVID-19 event of which 3.8% (n=37,418) had a COVID-19 related hospitalisation and 2.2% (n=21,116) died. A marginally lower risk of COVID-19 death was observed for those with pre-existing AT use which directionally aligns with the most comparable previous studies[9,11]. AT use was, however, associated with higher odds of COVID-19 hospitalisation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Of the AF cohort analysed, 8% (n=77,364) had a recorded COVID-19 event of which 3.8% (n=37,418) had a COVID-19 related hospitalisation and 2.2% (n=21,116) died. A marginally lower risk of COVID-19 death was observed for those with pre-existing AT use which directionally aligns with the most comparable previous studies[9,11]. AT use was, however, associated with higher odds of COVID-19 hospitalisation.…”
Section: Discussionsupporting
confidence: 87%
“…For DOACs vs warfarin, no difference was observed between groups for COVID-19 death, but DOACs were associated with marginally reduced odds of COVID-19 hospitalisation. Our analysis did not directly investigate the previously reported observation that vitamin K depletion through warfarin is harmful[15] but, more generally, our findings suggest that it is unlikely that warfarin offers protection against severe COVID-19 outcomes compared with DOACs[11].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The ability of CHA 2 DS 2 -VASc to discriminate an individual’s future stroke risk is also only moderate (pooled area under the receiver operating characteristics curve (AUC) of 0.67 across 27 studies 14 ) and potentially lower for predicting first ever stroke based on information at the point of AF diagnosis where available evidence is significantly limited. Recent research has also observed that pre-existing use of antithrombotics, particularly anticoagulants, is associated with lower odds of people with AF dying from COVID-19 15,16 . A model that could improve prediction of first stroke in people with AF and also identify those at greatest risk of COVID-19 death would be a potentially valuable new tool to inform anticoagulant prescribing decisions.…”
Section: Mainmentioning
confidence: 99%